Tools for public social science in the digital age: interpretative strategies for content analysis in the public good (Intercom - Revista Brasileira de Ciências da Comunicação, 2026)
Digital platforms have grown into powerful forms of messaging and dissemination of discourse within and across important economies including the U.S. and Brazil. While big data approaches may give us the broad strokes presented with a host of quantitative measures, these strategies are not ideally suited researchers contributing to public-facing social sciences in which narrative, storytelling, and naturally occurring discourse are prominently featured. This research begins to fill this gap by offering content analysis strategies for such interpretively oriented qualitative researchers. In providing replicable methodological tools to analyze data interpretively, this research provides a toolkit for qualitative researchers engage in Public Social Science in an age of contentious politics.